A Deixis Analysis in Joko Widodo’s Speech on the Closing G20 Summit - Yolanda Trisna Dewi; Yuliyanto Sabat; Siti Aisyah; Yudy Prasetyo (Edu-Ling: Journal of English Education and Linguistics, 2023)
Deixis become an important function in oral communication. They can resolve confusion, ambiguity, and misunderstanding on meaning of utterances. Among the many formal communication forms, the speech of President Joko Widodo in G20 Summit closing event can become interesting to research in term of deixis study. This article investigates the type of deixis and what deixis is the most dominantly used in the speech of Joko Widodo at the G20 Summit closing. The data were described qualitatively by referring to Levinson. Using Miles and Huberman's interactive mode, the finding shows that among 47 of deixis used, person deixis was 25, temporal deixis 3, social deixis 14, and discourse deixis 5. Person deixis “I” was found to be the most dominant in the speech, which indeed conclude that President Joko Widodo showed himself the the holder of the mandate for holding the G20 Summit in Indonesia. Keywords: Deixis, Types of Deixis, Joko Widodo, G20 Summit